Copper-catalyzed annulation of 2-bromobenzoic esters with terminal alkynes towards 3-substituted isocoumarins. Issue 25 (21st June 2017) - Sun, Mengli; Su, Lebin; Dong, Jianyu; Liu, Long; Zhou, Yongbo; Yin, Shuang-Feng
Graphical abstract: Highlights: A highly convenient synthesis for 3-substituted isocoumarins under mild conditions. 2-Bromobenzoic esters show higher efficiency and regioselectivity than those of 2-bromobenzoic acids. Abstract: An efficient method for the synthesis of 3-substituted isocoumarins that are an important class of biologically active scaffolds via annulation of 2-bromobenzoic esters with terminal alkynes by copper catalyzed is described. The advantages of this method include mild reaction conditions, high yield and regioselectivity, and wide tolerance toward functional groups.